2010
DOI: 10.1093/jac/dkq279
|View full text |Cite
|
Sign up to set email alerts
|

Azole antifungal resistance in Aspergillus fumigatus: 2008 and 2009

Abstract: Azole resistance is evolving and growing in frequency. Established and novel mechanisms may be responsible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
256
6
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(272 citation statements)
references
References 11 publications
6
256
6
4
Order By: Relevance
“…It has not yet been clearly demonstrated that the beneficial effects of azoles in ABPA and SAFS are due to their antifungal activity as opposed to alterations in concomitantly administered glucocorticosteroid metabolism or independent anti-inflammatory azole effects [43,51]. Most troubling, however, is the emerging evidence that increased azole usage for various medical conditions and (at least in some geographical regions) agricultural applications is leading to a higher prevalence of azole resistance in clinical A. fumigatus isolates, most commonly due to point mutations in the cyp51A gene [100][101][102][103][104][105][106][107][108]. The Aspergillus cyp51A gene encodes cytochrome P450 sterol 14a-demethylase and is the target for azole drugs.…”
Section: Antifungal Therapy In Abpa and Safsmentioning
confidence: 99%
“…It has not yet been clearly demonstrated that the beneficial effects of azoles in ABPA and SAFS are due to their antifungal activity as opposed to alterations in concomitantly administered glucocorticosteroid metabolism or independent anti-inflammatory azole effects [43,51]. Most troubling, however, is the emerging evidence that increased azole usage for various medical conditions and (at least in some geographical regions) agricultural applications is leading to a higher prevalence of azole resistance in clinical A. fumigatus isolates, most commonly due to point mutations in the cyp51A gene [100][101][102][103][104][105][106][107][108]. The Aspergillus cyp51A gene encodes cytochrome P450 sterol 14a-demethylase and is the target for azole drugs.…”
Section: Antifungal Therapy In Abpa and Safsmentioning
confidence: 99%
“…Austria, Belgium, Denmark, France, Germany, the Netherlands, Norway, Spain and Turkey), the USA, South America and Asian countries (e.g. China, India, Iran, Japan and Kuwait), with an incidence rate of 3.3-38 % (Badali et al, 2013;Bader et al, 2013;Bueid et al, 2010;Burgel et al, 2012;Chowdhary et al, 2011;Chryssanthou, 1997;Howard et al, 2009;Lockhart et al, 2011;Mortensen et al, 2010;Pham et al, 2014;Seyedmousavi et al, 2013;Snelders et al, 2008;van der Linden et al, 2011;van Ingen et al, 2014). According to a recent international surveillance study on the clinical isolates of azole-resistant A. fumigatus, an incidence rate of 3.2 % was reported, which introduced a novel phase in the management of invasive aspergillosis (van der Linden et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Over 90 % of azole-resistant A. fumigatus isolates harbour a leucine-to-histidine substitution at codon 98, along with a 34 bp tandem repeat in the CYP51A promoter region. This issue, which is associated with high rates of treatment failure, has become a major medical concern (Howard et al, 2009;Snelders et al, 2009;van der Linden et al, 2011;Verweij et al, 2007). However, a novel CYP51A-promoter duplication mutation, known as TR 46 /Y121F/T289A, has recently been introduced, which is considered responsible for the elevated MIC of voriconazole (Chowdhary et al, 2013;van der Linden et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In addition, a growing number of azole-resistant A. fumigatus strains has been identified in Europe over the past decade, contributing significantly to treatment failure. [9][10][11][12][13] Preclinical in vivo studies are indispensable for gaining a better understanding of the pathogenesis of infections caused by both azole-susceptible and -resistant strains and for assessing their response to antifungal drugs. However, the gold standard techniques used for evaluation of infections in small animal models, such as fungal load quantification by colony-forming unit (CFU) counts, galactomannan (GM) antigen detection and microscopy of tissue sections, have limitations.…”
mentioning
confidence: 99%